Compaction behaviour of mannitol-cocoa powder mixtures and their resulting tablet strength and disintegration characteristics - Mukri, Ahmad Kamal; Tan, Jie Hong; Mohd Tahir, Suraya; Anuar, Mohd Shamsul; Mohd Yusoff, Syamimi (Rynnye Lyan Resources, 2021)
Cocoa powder is an important ingredient in the confectionery industry and, mannitol is an alternative sugar alcohol. In this work, mannitol powder was mixed with cocoa powder and compacted into tablet form via the uniaxial die compaction process. The frictional, compaction, tablet mechanical and disintegration properties were studied due to their importance in characterizing the behaviour of the tablets during processing and its final product characteristics at varying mannitol contents. The composition of mannitol in the mannitol-cocoa tablet varied at 95% w/w, 50% w/w and 5% w/w, while pure 100% w/w mannitol and cocoa tablets were set as controls. The compaction pressures used in making the tablets varied at 37.67 MPa, 75.34 MPa, 113.01 MPa, 150.68 MPa and 188.35 MPa. The compaction behaviour of the powder during the compaction process was evaluated using the plastic work and the maximum ejection stress values. The tablet strength was determined using the tensile strength method and tablet disintegration study was also conducted. The results showed that the increase in the compaction pressures increased the plastic work, maximum ejection pressure, tablet strength and also its disintegration time. The tablet formed having 95% w/w mannitol composition exhibited the highest plastic work value of 10.32±0.01 J, highest maximum ejection pressure value of 4.4±0.06 MPa, highest tensile strength value of 1.06±0.04 MPa and shortest disintegration time of 171±51 s amongst the three different mannitol compositions studied. Meanwhile, the effects of mannitol composition in the tablet on these observed responses were also dependent upon the compaction pressures used during tablet formation. In conclusion, the addition of mannitol improved the tablet strength and shorten the disintegration time in the experimental range employed in this study.